Taking Into Account the Effects in Field of Improvement of Quality Environment in Opinion of Efficiency of Undertakings - Graczyk, Andrzej (Regional Barometer. Analyses & Prognoses, 2012)
The analysis of effects and the range of opinion derived from different efficiency areas while considering, at the same time, the environment’s quality improvement. The range of defining the effects is introduced in the first part. The second part discusses the areas of occurrence of opinion of efficiency (technical efficiency, energy, financial, economic). The third part concerns the problem of qualifying ecological efficiency.